Antimicrobial resistance: a critical public health challenge in Albania - Shapo, Leidon; Brati, Blerta (The Journal of Infection in Developing Countries, 2026)
Antimicrobial resistance (AMR): AMR represents a critical challenge for healthcare systems globally and in Albania. The increasing ability of microorganisms to withstand standard therapies complicates infection management, elevates morbidity and mortality, and drives up healthcare costs. Overprescribing and incomplete antibiotic courses are principal contributors, underscoring the necessity for robust stewardship and ongoing education. Continued research and the development of novel antimicrobials are essential. Growing concern: AMR is exacerbated by inappropriate antimicrobial use, suboptimal infection control, and global mobility. Both human and veterinary medicine are affected, with resistance spreading via direct contact and the food chain. The “One Health” approach-integrating human, animal, and environmental health-is essential for effective AMR management; and without intervention, AMR could result in millions of deaths annually. The major drivers of AMR include (i) unnecessary prescriptions and incomplete treatment courses; (ii) poor hygiene and infection control in clinical settings; (iii) international movement of people and goods; and (iv) limited development of new antimicrobial agents. Albania is experiencing rising rates of antibiotic resistance, particularly in urinary tract infections (UTIs) and community-acquired pathogens. Excessive antibiotic prescribing among certain healthcare professionals highlights the need for improved stewardship and adherence to clinical guidelines. The National Action Plan on AMR exists, but its implementation requires further evaluation. Conclusions: Albania has established a functioning AMR surveillance system and continues to implement awareness campaigns. Ongoing research and targeted interventions are needed to address resistance trends. Strengthening stewardship and surveillance is critical to mitigating the impact of AMR on patient outcomes and public health.